(untitled) (Herald of Journalism, 2016)
The traditional division of media policy and the telecommunication policy become outdated. The digital, multimedia interactive communica-tion technology expands the borders between the countries, becomes more accessible in different regions of the world. There is a merger between transferring channels both telephone, and cable networks. The sector of Mass Communication becomes exchange capable and inter additional. Change of nature of communication became feature of new mass media. It is difficult to distinguish the mass and personal form of communications. Consumption of new media has more individual and interactive character. The rapid development of a blog sphere, civil journalism in Kazakh-stan is a striking example. The number of users of social media is growing. Facebook became the most advanced social network in Kazakhstan, the second place takes on VK, and the third position belongs to a network of microblogs – Twitter.